Integration of Artificial Intelligence in Mathematics Learning : Systematic Literature Review : Integrasi Artificial Intelligence (AI) dalam Pembelajaran Matematika : Systematic Literature Review - Sutomo, Woro Anglia Banda; Turmudi, Turmudi (SJME (Supremum Journal of Mathematics Education), 2025)
The integration of artificial intelligence (AI) in mathematics learning introduces a new paradigm in mathematics education by utilizing technology to broaden and enrich students learning experience. This study is a systematic literature review. The objective of this study is to provide in-depth insights into the integration of artificial intelligence in mathematics education and to establish a foundation for further research and development in this field. Based on the analysis of publication status, we found five research articles that examine the use of artificial intelligence (AI) in mathematics education across various educational levels, published in 11 international journals indexed by Scopus. One of the commonly used approaches is AI-driven game-based learning, alongside various other AI technologies. In the context of educational levels, unior high school stands out as the primary focus for the implementation of AI technology. Therefore, this Systematic Literature Review (SLR) provides valuable insights for further development in the integration of AI in mathematics education.